The Intertwined Between Online Gambling and Online Loans (Qualitative Study of College Students in Medan City) - Nurbani; Wijaya, Haris; Ananda, Sabilla Tri (Komunika, 2024)
Online loans are loans through online application or website with simple requirements. This could be a magnet for online gambler that have been singificanlty increased, especially in this research focus, among college students. This qualitative research aims to explain about the existence of online loans in generate temporary financial security for college students who plays online gambling in Medan City, as for online gambling, positively associated with online loans. Based on data that collected through interview and observation from several informants, it can be conluded that there are various online loans positions towards online gamblers. To begin with, online loans keeps online gamblers to play continuously since it provides sustainable financial resources. On the other hand, it also creates the anxiety among online gambler due to an inability to pay their online debts when the players defeated in online gambling and this situation leads to not only a financial stress among online gamblers, but also the addiction to play even more to gain a winning to pay their debts. This research also suggested that authorized party needs to emphasize a firm regulation about online gambling that can reduce the negative effect of both online gamblings and online loans that help to reduce the growth of negative association between online loans and online gamblings.